Personality traits as a predictor of emotional intelligence among medical students - Neha Taneja; Sujata Gupta; Vinoth Gnana Chellaiyan; Aanchal Anant Awasthi; Sandeep Sachdeva (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Emotional intelligence (EI) is the ability to understand and manage our own feelings and of others. It has emerged as one of the vital elements of success and interpersonal relations in everyday life. There are individual differences of EI depending on characteristics and behaviors of an individual, which determines their personality. AIMS AND OBJECTIVES: The present study assesses the EI and personality traits of medical students and determines the relationship of EI with personality traits of the medical students. MATERIALS AND METHODS: This was a cross-sectional study and was conducted among students of a government medical college, located in New Delhi. A total of 210 participants were included in the study. After obtaining written informed consent from all participants, a questionnaire consisting of demographic information, Ten-Item Personality Inventory and Schutte EI Scale, was administered. The means and proportions were calculated. Chi-square test and Pearson's correlation test were used to test significance. P < 0.05 was considered statistically significant. RESULTS: The mean (standard deviation) age of the study participants was 21.54 (±1.98) years. The majority (65.7%) of the students were male. 51% of the students had moderate EI, and high EI was seen in 49% of the students. A positive and significant relationship between personality traits and EI was found in the study. CONCLUSION: Personality traits and EI are related to one another and could influence student academic achievement. Since EI influences academic performance so personality trait assessment and empathic perceptions exploration can facilitate to aid the academic performance of the students.